Influence of abiotic factors in Calliphoridae and Mesembrinellidae (Insecta: Diptera) entomofauna in the Jardim Botânico do Rio De Janeiro, Brazil - Adriana Leal de Figueiredo; Jéssica da Silva Costa; Wellington Thadeu de Alcantara Azevedo; Maria Lucia França Teixeira; Cláudia Soares Santos Lessa; Valéria Magalhães Aguiar (PLoS ONE, 2025)
Diptera are one of the four megadiverse insect orders, with great environmental, ecological, forensic and medical-sanitary relevance. The Jardim Botânico do Rio de Janeiro, located in an urban area of Rio de Janeiro, Brazil, constitutes an important refuge, supporting the conservation of several species. Through the knowledge of the diversity of Calliphoridae and Mesembrinellidae in this location, it will be possible to identify the behavior of native species along with the invasive genus Chrysomya, and to evaluate the influence of abiotic factors (temperature, relative humidity and pluviosity) on insect capture. Eight traps containing sardines were set and a total of 36,035 Diptera specimens were collected, of which 35,890 were of the Calliphoridae family and 145 of the Mesembrinellidae family. The average abiotic variables recorded were: Temperature 25,6 ºC (± 3,17), humidity 68% (±9,33%) and rainfall 3.42 mm (± 7,99). The total abundance of Calliphoridae and Mesembrinellidae peaked during January 2015, with the highest temperature. Among the variables and abundance and richness indices, significant results were only observed between temperature and abundance. None of the variables showed significant correlation with Calliphoridae and Mesembrinellidae richness. The presence of some species of Calliphoridae and Mesembrinellidae indicates the area’s good conservation status as they only occur in highly preserved forest areas. Through the knowledge of their richness and abundance, new legislation can be developed to help conservation efforts in deeply modified environments.